2022
DOI: 10.1155/2022/5096406
|View full text |Cite|
|
Sign up to set email alerts
|

Influences of Airway Obstruction Caused by Adenoid Hypertrophy on Growth and Development of Craniomaxillofacial Structure and Respiratory Function in Children

Abstract: Adenoid hypertrophy (AH) is a common disease in otorhinolaryngology. Children with chronic snoring and hypoxia are susceptible to long-term nasal obstruction, while long-term open-mouth breathing may cause craniofacial bone development disorders and dull facial expressions, the so-called adenoid face. The purpose of this work is to analyze the influence of AH-induced airway obstruction (AO) on the growth and development of craniomaxillofacial structure and respiratory function (RF) in children. The clinical da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Similarly, other workers in Lebanon reported severe symptom scores in 85.7% of younger children versus 29.2% of older children [13]. This agreement may be due to narrower nasopharyngeal space, repeated episodes of upper respiratory tract infections, and increased immunological activity in this age group [6,17]. This research also showed a significant difference in terms of symptomatology scores between the younger and the older http://doi.org/10.33091/amj.2024.144909.1456 age groups (χ 2 = 28.099, P-value = 0.000).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, other workers in Lebanon reported severe symptom scores in 85.7% of younger children versus 29.2% of older children [13]. This agreement may be due to narrower nasopharyngeal space, repeated episodes of upper respiratory tract infections, and increased immunological activity in this age group [6,17]. This research also showed a significant difference in terms of symptomatology scores between the younger and the older http://doi.org/10.33091/amj.2024.144909.1456 age groups (χ 2 = 28.099, P-value = 0.000).…”
Section: Discussionsupporting
confidence: 56%
“…Obstructive adenoid enlargement affects children in different ways; it obstructs the nasopharyngeal airway passage resulting in nasal obstruction, recurrent rhinorrhea, persistent mouth breathing, snoring, sleep-disordered breathing, obstructive sleep apnea, daytime somnolence and then poor school performance [4,5]. It was reported that adenoid enlargement is the most common cause of sleep problems in chilhttp://doi.org/10.33091/amj.2024.144909.1456 dren, and sleep problems on the other hand have been implicated in major health consequences such as reduced alertness, memory, and learning deficits [6,7]. Therefore, diagnosis of obstructive adenoid enlargement should be achieved as early as possible to avoid these problems.…”
Section: Introductionmentioning
confidence: 99%
“…They gradually increase in size as we age, reaching their peak dimensions at around 6 to 7 years old. Subsequently, these critical tissues undergo a process of atrophy, ultimately merging with the mucosa of the nasopharyngeal wall [ 14 ]. Traditionally, the behavior of the pharynx has been attributed to Bernoulli’s theorem.…”
Section: Adenoids and Tonsils: Unraveling The Complexities Of Airway ...mentioning
confidence: 99%
“…A study has demonstrated a correlation between the degree of nasal obstruction in children with primary snoring and changes in cephalometric parameters related to vertical craniofacial growth [ 39 ]. As ATH compels children to rely on mouth breathing as their primary mode of respiration, some researchers propose that prolonged mouth breathing can lead to abnormal development of the maxillofacial bone structure [ 14 ] ( Figure 1 ). Furthermore, the very act of breathing plays a crucial role in the mechanism of pharyngeal collapse, an essential aspect of OSA [ 40 ].…”
Section: Adenoids and Tonsils: Unraveling The Complexities Of Airway ...mentioning
confidence: 99%
“…This article has been retracted by Hindawi, as publisher, following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of systematic manipulation of the publication and peer-review process.…”
mentioning
confidence: 99%